Slovenian Entrepreneurship Observatory 2002 - Rebernik, Miroslav; Močnik, Dijana; Knez Riedl, Jožica; Širec, Karin; Rus, Matej; Tominc, Polona; Krošlin, Tadej (University of Maribor Press, 2003)
Observatory provides an overview and analysis of the current situation in small and medium-sized enterprises in 2001. The situation in Slovenia was compared to that of SMEs in the European Union. In doing this, data gathered in the Observatory of European SMEs has been used, together with its basic methodology, which consists of three areas: standard topics included in the report every year, special in-depth studies chosen each year, and various other topics that may vary through time or represent a supplement to the existing relevant topics. The publication provides a standard review of Slovenian entrepreneurship in 2001 and a detailed description of tax incentives, administrative burdens for small and medium-sized enterprises in the area of recruitment and social responsibility of SMEs. The survey that was carried out was based on 1,153 analyzed responses, which were acquired by sending out 8,176 questionnaires. Study show that Slovenian small and medium-sized enterprises are more often involved in responsible social activities than European one, but also that almost half of small enterprises do not invest in research and development. Our research has also shown high administrative burdens faced by SMEs.